Effect of Programmed Exercise through Telerehabilitation at Home on Visual Analogue Scale, Body Mass Index, and WOMAC among Patients with Obesity and Knee Osteoarthritis: A Quasi-Experimental Study - Sasono, Binar; Tamin, Tirza Z; Harini, Melinda; Rachmawati, Maria Regina (Acta Medica Indonesiana, 2026)
Background: This study aims to determine the effectiveness of programmed exercise with telerehabilitation at home in patients with obesity and knee osteoarthritis on visual analogue scale scores, body mass index, and Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC). Methods: This research is a pre–post study in patients with obesity and knee osteoarthritis. Research subjects performed a series of exercise programs at home for 28 days. Before the program, there was an initial assessment from a psychologist and a nutritionist. During the program, there was tele-education, telemonitoring, and teleconsultation from doctors. Twenty-six female subjects participated. Results: Visual analogue scale scores decreased statistically significantly every week, until the end of the fourth week, compared with before the intervention (p<0.001). Body mass index and WOMAC scores decreased statistically significantly at the end of the fourth week compared with before the intervention (both p<0.001). Further analysis of all WOMAC components in the intervention group, including pain, stiffness, and physical function, also showed a statistically significant decrease (p<0.001). Conclusion: Programmed exercise as part of telerehabilitation at home has been statistically proven to reduce visual analogue scale scores, body mass index, and WOMAC in patients with obesity and knee osteoarthritis.